2020
DOI: 10.18699/vj19.581
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of <i>mariner</i>-like elements in Orthoptera

Abstract: Mariner-like elements (MLEs) are among the most widespread DNA transposable elements in eukaryotes. Insects were the first organisms in which MLEs were identified, however the diversity of MLEs in the insect order Orthoptera has not yet been addressed. In the present study, we explore the diversity of MLEs elements in 16 species of Orthoptera belonging to three infraorders, Acridoidea (Caelifera), Grylloidea (Ensifera), and Tettigoniidea (Ensifera) by combining data mined from computational analysis of sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Other than life history and ecology, genome size has been hypothesized to correlate with traits of cytogenetics and genome architecture. Several studies found large genomes, including those of orthopterans, rich in satellite DNA, long terminal repeats and transposons, including helitrons and mariner like elements [9,10,[47][48][49]. Whole genome duplications are another presumably common reason for large genome size (e.g., in fish [50]), going along with a polyploidization and a large number of chromosomes.…”
Section: The Relationship Of Genome Size With Life History and Cytoge...mentioning
confidence: 99%
“…Other than life history and ecology, genome size has been hypothesized to correlate with traits of cytogenetics and genome architecture. Several studies found large genomes, including those of orthopterans, rich in satellite DNA, long terminal repeats and transposons, including helitrons and mariner like elements [9,10,[47][48][49]. Whole genome duplications are another presumably common reason for large genome size (e.g., in fish [50]), going along with a polyploidization and a large number of chromosomes.…”
Section: The Relationship Of Genome Size With Life History and Cytoge...mentioning
confidence: 99%
“…Other than life history and ecology, genome size has been hypothesized to correlate with traits of cytogenetics and genome architecture. Several studies found large genomes, including those of orthopterans, rich in satellite DNA, long terminal repeats and transposons, including helitrons, and transposons, and mariner like elements (9,10,(47)(48)(49). Whole genome duplications are another presumably common reason for large genome size (e.g.…”
Section: The Relationship Of Genome Size With Life History and Cytoge...mentioning
confidence: 99%